Access to credit and value additions to some non-timber forest products in Egbeda Local Government Area, Nigeria (2012)
The capacity to promote sustainable use of Non-Timber Forest Products (NTFPs) and facilitate increased financial benefits to local users as incentives for forest conservation is low due to neglect by governments particularly in Nigeria. Such capacity is however imperative to stemming rural poverty and can be enhanced by incorporating NTFP collection and commercialization research into forest management development programs. But sustainable production and conservation of forest products is influenced by a number of factors, largely socioeconomic and institutional in nature. Men and women also play different roles in the collection and utilization of NTFPs. This paper reports collection and sales of NTFPs against some socioeconomic background of identified collectors in Egbeda Local Government Area (LGA), Oyo state, Nigeria. Purposive simple random sampling was used to select respondents from the study population using the medium of the Egbeda Farmers Association of Nigeria (EFAN). Egbeda LGA has 10 cell groups of EFAN and twelve (12) farmers were selected from each of the cell group. A total of 120 sets of structured questionnaire were used to document demographic information, involvement in NTFPs business and access to credit facilities among respondents. Oral interview were also conducted to know if they engage in the NTFPs business as a primary occupation or secondary occupation, the type of NTFPs specialized in, their sources, number of gathering trips per week, and the amount made from the sales of the NTFPs. The data collected was analyzed using descriptive and inferential statistics. More than half (53.3%) of the respondents involved in the NTFPs business in the study area was of the male gender and 62.5% had secondary education. Majority of the respondent (88.2%) engaged in NTFPs gathering as a secondary occupation. Their access to credit facilities was low. The amount made from sales without credit facilities is reasonable. Inadequate funding, lack of credit facilities, inadequate information about how to market their products and its neglect by government were identified as a major constraints to sustainable collection and use of NTFPs. NTFPs would contribute more to livelihood in the study area, provided access to credit can be facilitated.